Pengaruh Kepercayaan Dan Kemudahan Terhadap Keputusan Pembelian Online Melalui Aplikasi Shopee - Wuri Purnamasari (Fakultas Ekonomi Universitas 45 Surabaya, 2023)
Advances in information technology, including the internet, have had a significant impact on various fields, including developments in the world of business and marketing. This research aims to determine the influence of trust and convenience on online purchasing decisions via the Shopee application. The method used in this research is a quantitative method and the assessment of the results of this research is based on respondents' answers using a Likert scale. The population in this research are Gunadarma University students who have used or are currently using the Shopee application. The analytical tools used are Validity Test, Reliability Test, Classical Assumption Test (Normality, Multicollinearity, Heteroscedasticity), Multiple Linear Regression Analysis, F Test, T Test, and Coefficient of Determination Test. Based on the results of static data analysis, this research variable is valid and reliable, in the classic assumption test no multicollinearity and heteroscedasticity were found and it was normally distributed. The research results show that partially (t test) states that the Trust variable (X1) has a significant effect on online Purchasing Decisions (Y) in the Shopee application, while the Convenience variable (X2) has a significant effect on online Purchasing Decisions (Y) in the Shopee application. Simultaneously (F Test) states that the variables Trust (X1) and Convenience (X2) have a significant effect simultaneously or together on online Purchasing Decisions (Y) in the Shopee application.